Welcome, how are you doing? – towards a systematic mental health screening and crisis management for newly arriving refugees. Issue 2 (23rd November 2023) - Schmidt, Telja Lucia; Catani, Claudia; Dumke, Lars; Groß, Melissa; Neldner, Sina; Scharpf, Florian; Weitkämper, Angelina; Wilker, Sarah; Wittmann, Jasmin; Stammnitz, Anke; van den Heuvel, Rick; Neuner, Frank
ABSTRACT: Background: Compared to the general German population, refugees in Germany are a high-risk group for trauma spectrum disorders. Currently, many barriers exist for the implementation of a screen-and-treat approach for mental disorders as part of the routine health care provision during the early stage of the immigration process. Objective: The aim of the present study was to develop and test a systematic screening approach to identify individual refugees in need of mental health care during the initial immigration phase. Method: 167 newly arrived refugees underwent a screening interview with the Refugee Health Screener (RHS) carried out by Intercultural Therapy Assistants (ITAs). The ITAs were supervised by psychologists at a reception centre in Bielefeld, Germany. A subsample of 48 persons participated in clinical validation interviews. Results: Findings demonstrated the need for and feasibility of a systematic screening during the initial immigration phase. However, established cut-off values of the RHS had to be adapted and the screening procedure had to be adjusted due to the needs of a significant number of refugees in severe psychological crises. Conclusion: A systematic screening that is applied shortly after arrival facilitates the early identification of refugees at risk of developing mental disorders and may be helpful to prevent chronic symptom development and an aggravation of psychological crises. HIGHLIGHTS : A systematic complementary screening procedure during the initial immigration phase was found to be useful for the identification of refugees in need of mental health care. The procedure could be implemented both safely and efficiently in conjunction with the initial medical check-up for recently arrived refugees. Responding to the needs of the refugees immediately following their arrival in Germany, we adjusted the cut-off of the screening instrument and suggest to explicitly include a detection procedure for severe psychological crises.